Public expenditures and the performance of Latin American and Caribbean agriculture - Gustavo Anriquez; William Foster; Jorge Ortega; Cesar Falconi; Carmine Paolo de Salvo (Inter-American Development Bank (IDB), 2016)
Economic theory and econometric evidence support the thesis that the displacement of government expenditures on public goods by subsidies to private goods inhibits the performance of the farm sector. This paper presents an analysis of the influence of the mix of expenditures related to agriculture on net income generation, using data for 19 Latin American and Caribbean countries during 1985-2012. The econometric results demonstrate that total government spending on the farm sector positively impacts agriculture's performance. More importantly, and of greater practical economic significance, increasing the share of expenditures committed to public goods, ceteris paribus, would significantly raise rural income as measured by sector value added per capita of the rural population.
hdl:11319/7839
Keywords: H50; O13; Q16; Q17; Q18; 330; Public Expenditure; Agricultural Policy; Agriculture; Economic Development